A process for producing antioxidant and catechin extracts from Morinda citrifolia leaf - Abdul Hamid, Azizah; Pak Dek, Mohd Sabri; Saari, Nazamid; Osman, Azizah; Markom, Masturah (2010)
The present invention relates to a process for producing antioxidant and catechin extracts from Morinda citrifolia leaf. process for producing antioxidant and catechin extracts from a Morinda citrifolia leaf utilizing a supercritical fluid extraction (SFE), the process includes the steps of (a)pre-treating a sample Morinda citrifolia leaf, (b) conducting a SFE using carbon dioxide (CO2)and polar modifier for a period of approximately one to five hours, preferably three hours and collecting ethanol containing solute.